Fusobacterium necrophorum subsp. necrophorum Liver Abscess with Pylephlebitis: An Abdominal Variant of Lemierre’s Syndrome - Natasa Radovanovic; Igor Dumic; Mladjen Veselinovic; Susanne Burger; Tamara Milovanovic; Charles W. Nordstrom; Eric Niendorf; Poornima Ramanan (Case Reports in Infectious Diseases)
Liver abscess associated with suppurative portal vein thrombosis (pylephlebitis) secondary to Fusobacterium necrophorum has been rarely reported. It is considered to be an abdominal variant of Lemierre’s syndrome associated with significant morbidity and mortality. We report a case of 69-year-old man who developed liver abscess and pylephlebitis due to F. necrophorum with an unclear source of infection. We discuss the pathogenesis, diagnosis, and treatment strategy for this entity, with a review of previously published cases of pyelephlebitis due to F. necrophorum in regard to their clinical presentation and outcome.